Hairpin transcription does not necessarily lead to efficient triggering of the RNAi pathway - Dalakouras, Athanasios; Tzanopoulou, Maria; Tsagris, Mina; Wassenegger, Michael; Kalantidis, Kriton (Transgenic research, 2011)
Previously, we had shown that stable expression of a hairpin RNA sharing homology with the coat protein (CP) of the Cucumber mosaic virus (CMV) (hpRNACMV) produced CMV resistant Nicotiana tabacum plants. However, only 17% of the hpRNACMV-expressing plants generated substantial amounts of siRNAs that mediated CMV resistance (siRNAsCMV). Here, we demonstrate that the transcription of a hpRNACMV per se is not sufficient to trigger cytoplasmic and nuclear RNAi. A multiple-transgene copy line showed a strong resistance phenotype. Segregation of individual copies revealed that in one locus, the transgene-produced hpRNACMV transcript was processed into 21-nt and 24-nt siRNAsCMV and lines containing this locus were resistant. At a second locus, where the transgene was shown to be transcribed, no siRNAsCMV were produced and lines harbouring only this locus were susceptible. In addition, the second locus failed to trigger de novo RNA-directed DNA methylation (RdDM) in cis, of its cognate sequence. However, after being induced in trans, methylation in the transcribed region of the transgene was maintained in both CG and CHG residues. Sequence-specific maintenance of methylation in transcribed regions, as well as diverse RNA degradation pathways in plants are discussed in view of our observations.